(untitled) (Confluenţe Bibliologice, 2017)
The author reports about the „Indexing of subjects” Workshop on topics: problems and solutions, held during the satellite meeting of the Annual Conference of the Association of Librarians of the Republic of Moldova „We transform libraries - we transform communities”. The event was organized by the Education and Specialized Libraries Section of the ABRM in agreement with the BIN Branch (Northern Educational Libraries) - the Scientific Library of the Alecu Russo Balti State University. 38 librarians from the university and specialized libraries of the Republic of Moldova participated.